风机偏心对空冷梁式桥架振动实验研究 - 郭铁能; 孟令军; 白春生; 华旭 (Jixie qiangdu)
The vibration problem of air-cooling fan bridge has been troubling the north thermal power plant.Excessive vibration amplitude causes the damage of fan,motor,reducer and other equipment,and affects the stability and economic benefit of power plant operation.In this paper,the vibration speed of the air-cooling fan exceeded the standard as the research object,and the data acquisition instrument and acceleration sensor were used to test the vibration of the air cooling fan bridge in the power plant of xiaoyi in Shanxi Province.According to the frequency characteristics generated by these incentives,the main influence factors of the vibration of the fan bridge caused by the original fan blades were explored.By analyzing the vibration signal,the main influencing factors of the vibration of fan bridge are explored according to the frequency characteristics.The test results show that the excessive vibration of the bridge is caused by the interference force caused by the fan eccentric mass.During the operation of the fan,the phase of the sensor at the middle of the bridge alternates positively and negatively,and the fan shaft produces a sway,which is inconsistent with the expected horizontal vibration of the bridge.In order to verify the rationality of the above analysis,the finite element analysis of the bridge frame was carried out,and the results are consistent with the above conclusions.Through the forced vibration test and hammer test of the fan bridge,it is found that the maximum frequency value of the vibration of the fan bridge caused by eccentric mass is far away from the natural vibration frequency of the fan bridge,and will not cause the resonance phenomenon of the fan bridge.Therefore,the vibration of the fan bridge caused by eccentric mass is only related to the static stiffness of the fan bridge.The test results will provide a basis for the design of beam bridge and the avoidance of vibration caused by fan eccentricity.